2011
DOI: 10.1007/s11154-011-9171-7
|View full text |Cite
|
Sign up to set email alerts
|

Central leptin and ghrelin signalling: Comparing and contrasting their mechanisms of action in the brain

Abstract: In the past two decades, two major discoveries have greatly contributed to our current knowledge on the central control of food intake and body-weight; the discovery of the anorexigenic adipocyte derived hormone leptin in 1994 and the orexigenic gut derived hormone ghrelin in 1999. Both hormones act as crucial signals to indicate nutritional status as well as to modulate feeding behaviour through a variety of distinct pathways. They target overlapping CNS regions in order to mediate their obvious opposing effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 152 publications
(200 reference statements)
0
23
0
Order By: Relevance
“…Ghrelin and leptin are two hormones that have been recognized to have a major influence on energy balance [32,33]. Previous clinical studies involving SR showed inconsistent results as indicated by others [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin and leptin are two hormones that have been recognized to have a major influence on energy balance [32,33]. Previous clinical studies involving SR showed inconsistent results as indicated by others [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Also male progeny of dams exposed to HFA only slightly increased the intake of food, to a much lower degree than that observed in females, which was not enough to induce an increase in weight gain, as observed for female progeny of dams exposed to HFA. While the observed hyperleptinemia in male offspring of dams exposed to HFA may represent some degree of leptin resistance, and may eventually predict an increased risk of diabetes (Schmidt et al 2006), it may also exert some anorexigenic effect (Shan & Yeo 2011) and thus protect male offspring from overt hyperphagia and from concomitant excessive weight gain, upon early-life HFA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ghrelin and leptin, secreted from the endocrine cells of the stomach and the adipose tissues, respectively, are transported across the blood-brain barrier, and affect food intake via the hypothalamus. 45 They may also affect neurons in the memory regions of the brain including the hippocampus. 45 The current study presents another example.…”
Section: Discussionmentioning
confidence: 99%